GLOBAL FINANCIAL CRISIS AND INDIA’S CRISIS RESPONSES AND CHALLENGES - Sangeeta (Innovative Research Thoughts, 2023)
Financial performance is measuring the results of a firm's policies & operations in monetary terms. These results are reflected in the firm's return on investment, return on assets, value added etc. It is a subjective measure of how well a firm can use assets from its primary mode of business & generate revenues. This term is also used as a general measure of a firm's overall financial health over a given period of time, and can be used to compare similar firms across the same industry or to compare industries or sectors in aggregation. Financial reporting in govt. can be seen as a summary of the govt. performance, or capacity, in raising, handling and using public money. Governments issue many types of financial reports, but the most encompassing & visible at the state & local level is the Comprehensive Annual Financial Report (CAFR).